(untitled) (Horizontes de Enfermería, 2022)
Anxiety and depression are very common psychological disorders in adolescents that compromise their well-being and affect their way of life, these disorders can arise for various reasons such as stress, excessive worry, and other triggers. As a result of the emergence of the SARS-COV 2 virus, society faced several adverse situations that negatively affected the mental health of this vulnerable group. The objective of the present investigation was to analyze the psychological alterations in adolescents during the COVID-19 pandemic, for which a representative sample of 150 students was calculated so as to measure their anxiety and depression using Beck inventories, this allowed us to know that a significant level of students suffers from moderate and severe levels of these disorders, with the information obtained, a proposal for nursing interventions was developed based on the NANDA, NIC and NOC taxonomy aiming to achieve favorable results in the treatment of these conditions, these affectations are serious since they put people’s health and life at risk. For this reason, the proposed nursing interventions will allow a favorable and timely treatment to reduce the levels of anxiety and depression in adolescents by improving their quality of life and decreasing the incidence of these conditions.